2012
DOI: 10.2741/4000
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of Toll-like receptor signaling on distinct B cell subpopulations

Abstract: B cells exhibit a range of functional responses following TLR engagement including immunoglobulin and cytokine production, proliferation, antigen presentation and migration. However, B cell intrinsic TLR responses appear to be precisely programmed based upon the developmental stage of the cell. B cell subpopulations classified as innate immune cells including marginal zone and B-1 B cells exhibit robust responses to TLR stimulation. In contrast, activation of other B cell subsets is constrained via a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 121 publications
(185 reference statements)
1
27
0
Order By: Relevance
“…As expected, CD23 + B cells cultured with BLyS alone secreted minimal antibody, however, both TR and FO subsets secreted 10-fold more antibody following stimulation with either ODN 1826 plus anti-μ or STIC9 plus BLyS (Table 1 and Figure 4A, upper panel). Supernatants from MZ B cells revealed a similar pattern of Ig secretion, albeit at a greater magnitude, consistent with their vigorous response to TLR stimuli and propensity to undergo rapid plasma cell differentiation (56). Moreover, enzyme-linked immunosorbent spot (ELISPOT) analyses confirmed that ODN 1826 plus anti-μ or STIC9 plus BLyS induced antibody-secreting cell (ASC) formation ( Figure 4A, lower panel).…”
Section: Cd11csupporting
confidence: 49%
“…As expected, CD23 + B cells cultured with BLyS alone secreted minimal antibody, however, both TR and FO subsets secreted 10-fold more antibody following stimulation with either ODN 1826 plus anti-μ or STIC9 plus BLyS (Table 1 and Figure 4A, upper panel). Supernatants from MZ B cells revealed a similar pattern of Ig secretion, albeit at a greater magnitude, consistent with their vigorous response to TLR stimuli and propensity to undergo rapid plasma cell differentiation (56). Moreover, enzyme-linked immunosorbent spot (ELISPOT) analyses confirmed that ODN 1826 plus anti-μ or STIC9 plus BLyS induced antibody-secreting cell (ASC) formation ( Figure 4A, lower panel).…”
Section: Cd11csupporting
confidence: 49%
“…It is notable that expansion of a MZ-like B cell population was also observed in male BXSB mice bearing the trinitrophenyl/ ssDNA/ dsDNA-reactive Sp6 Ig Tg, irrespective of the presence of yaa [30]. Abnormal expansion or biology of murine MZ B cells, major autoIg producers [45] known to respond robustly to TLR ligands [46], has been linked to disease in some models [4754]. Of note, the hyperproliferation of our BXSB Tg B cells to B cell receptor crosslinking is unusual for MZ B cells, which normally undergo apoptosis in response to this stimulus [46].…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible explanations for this. In mice naïve and memory B cells express TLRs, hence the systemic dissemination of bacteria and bacterial products in sepsis can lead to their antigen-independent polyclonal activation [45 -48]. First, memory B cells, located primarily in the splenic marginal zone, may be re-activated [38,39].…”
Section: Resultsmentioning
confidence: 99%